Uyayi a collection of Philippine lullabies - Gutierrez, Chin-Chin (Makati City NCCA, 2003)
Disc 1 contains interpretations of the lullabies performed by Chin-Chin Gutierrez. Disc 2 features recordings from the original sources and a short "video journal" recounting the making of the project. The songs were selected to represent the different bioregions of the country, classified into burol (hills), kapatagan (plains), baybayin (coasts) and kabundukan (mountains).
CD 1. Tulala/Fendoyog medley / Teduray Traditional, arranger, Bo Razon ; Anak nga walay palad / Cebuano Traditional, arranger, Joey Ayala ; Uyayi ni Nena (Tulog na mahal ko) / Tagalog Traditional, arranger, Bo Razon ; Mendang na kong mendang / Pampango Traditional, arranger, Bo Razon ; Ili-ili tulog anay / Hiligaynon Traditional, arranger, Bo Razon ; Maglangan-langan ako / Tausug Traditional, arranger, Chin-chin Gutierrez ; Sa Duyan / Tausug Traditional, arranger, Tots Tolentino ; Kalipay / Ilonggo Traditional, arranger, Bo Razon ; Dayunday / Maguindanao Traditional, arranger, Malou Matute ; Sa ugoy ng duyan / L. San Pedro, L. Celerio, arranger, Tots Tolentino ; Nungka sa buhay ko / Bikolano Traditional, arranger, Rachel Conanan ; Dungdungan kanto / Ilokano Traditional, arranger, Rachel Conanan ; Katurog na, Entoy / Waray Traditional, arranger, Bo Razon ; Hohoyyawe / Ifugao Traditional, arranger, Bo Razon ; Dilay-en / Tala-andig Traditional, arranger, Joey Ayala ; Uwawi / Kalinga Traditional, arranger, Bo Razon ; Hud hud manait / Ifugao Traditional, arranger, Bo Razon -- CD 2. Dayunday / Maguindanaon ; Didedido sa lumbay / Maranao ; Maglanganlangan ako / Tausug ; Papanok / Maguindanaon ; Pamparampampa / Maranao ; Si nanay si tatay / Bikolano ; Tikuna ni nanang / Ilocano ; Inlugod ning Indo / Kapampangan ; Katuday / Ilocano ; Turog na aki / Bikolano ; O inay / Tagalog ; Matudtud ka anak / Kapampangan ; Lulabay / Ilocano ; Ni nanang ko / Ilocano ; Ili-ili / Hiligaynon ; Tulala / Teduray ; Blala flowiken / Teduray ; Kanta sa bata / Ata Lumad ; Giporongad / Matigsalog ; Pagyaya nog bata kon / Subanon ; Ibid Tuduk / T'boli ; Pagdawot / Mandaya ; Dilay-on / Talaandig Bukidnon ; Patulogon sa bata / Matigsalog ; Nguk ngukay / Arumanon ; Tumulog na bata kon / Subanon ; Fendoyog / Teduray ; Mobalet / Teduray ; Sa duyan / Hanunuo Mangyan ; Hibaniig / Kiangan Ifugao ; Hudhud Manait / Banaue Ifugao ; Hohoyyawe / Kiangan Ifugao ; Unga ad Ugaban / Banaue Ifugao ; Hohoyyawe / Kiangan Ifugao ; Uwawi / Butbut Kalinga.
Compact disc.
"Limited edition double disc with video journal" -- Container.
Subtitle and publishing information from container insert.
Lyrics in Philippine languages with English translation on container insert.
Program notes (24 p. : col. ill.) inserted in container.
Gift- Chin-chin Gutierrez April 20, 2004. For U.P. College of Music Library, a wellspring "Bucal" of our Motherland's heartsongs, the river that is never lost, never forgotten. Chin-chin, April 2004.
Keywords: Lullabies -- Philippines; Folk songs -- Philippines; Philippine languages -- Music; Songs -- Philippines